Calculation method of stress and deformation of hinged frame beams based on Winkler model - Wang, Benqian; Kang, Shibin; Tan, Peng; Liu, Guozeng (Archives of Civil Engineering, 2026)
Abstract: Based on Winkler foundation model, the mechanical model and coordinate system of hinged prefabricated anchor frame beam were established in order to quantitatively study the mechanical deformation characteristics of hinged prefabricated anchor beam. The mechanical model of hinged frame beams is simplified to Winkler elastic foundation beams. First, the general solution of beam bottom displacement is obtained by establishing the differential equation of beam deflection line, and then the general solution for rotation angle, bending moment and shearing force of the beam is obtained according to the relationship among beam bottom displacement, rotation angle, bending moment and shear force. The motion equation for the beam is derived based on the boundary and continuity conditions of the hinged frame beam. Then, the difference of structural characteristics between hinged frame beams and traditional frame beams under different anchoring forces is compared. Finally, the influence of external factors (anchorage force, foundation reaction coefficient) and internal factors (section size, cantilever length, hinged position) on the stress and deformation characteristics of the frame beam is compared, and the influence law of various factors is obtained by comparison, which provides a reference for the standardized design of the hinged frame beam.